Regulatory Dynamics of Special Mining Business Permits: Legal Developments and Emerging Challenges - Nabila Annisa Fuzain; Tundjung Herning Sitabuana (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2026)
This study examines the evolving legal framework governing the priority allocation of Special Mining Business License Areas (WIUPK) in Indonesia. It focuses on the paradigm shift from Law Number 3 of 2020, which restricted priority rights to State-Owned Enterprises (BUMN) and Regional-Owned Enterprises (BUMD), to the subsequent reforms introduced through Government Regulation Number 25 of 2024 and Law Number 2 of 2025. Employing normative juridical research with statutory and conceptual approaches, this study analyzes the hierarchy, coherence, and implications of the relevant legal instruments. The findings reveal a significant transformation in Indonesia's mining law politics through the expansion of priority recipients to include religious community organizations, cooperatives, micro, small, and medium enterprises (MSMEs), and business entities affiliated with higher education institutions. The study further demonstrates that Government Regulation No. 25 of 2024 initially generated a normative conflict with the prevailing Mining Law, creating legal uncertainty regarding the legitimacy of such preferential treatment. This antinomy was subsequently resolved through the enactment of Law No. 2 of 2025, which institutionalized the expanded priority scheme as a form of affirmative action aimed at promoting more equitable distribution of welfare derived from natural resource management. The study contributes to the discourse on mining governance by illustrating how affirmative regulatory policies reshape access to strategic mineral resources while redefining the relationship between legal certainty and distributive justice in Indonesia's extractive sector.